1998
DOI: 10.2466/pms.1998.86.2.563
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Dyschromatopsia and School Achievement

Abstract: In 1993-94, in Liguria (a northwestern Italian region) a study was carried out on dyschromatopsia, a congenital sex-linked form of colour blindness. 3124 junior high school boys aged 10-15 years were tested using Ishihara plates (1973 edition) and Farnsworth's D-15 test (1947 edition). 152 students were identified as colour blind (4.87%), a value slightly below the Italian average of 5.3%. The school achievement of these students was assessed by means of the school marks of two randomised subsamples composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…A literature review conducted in 1992 reported that studies attempting to relate CVD to learning difficulty were equivocal in their outcome [19]. A subsequent study in 1998 showed significantly lower general academic scores among 82 children with CVD as compared to 82 children with NCV, matched by age and class [20]. In contrast, a 2004 cohort study on 499 CVD children found that CVD did not cause significantly lower scores in mathematics and reading at 7 years and 16 years of age respectively, even after adjusting for birth-weight, social class at birth, family size, and parental education [21].…”
Section: School Agementioning
confidence: 99%
“…A literature review conducted in 1992 reported that studies attempting to relate CVD to learning difficulty were equivocal in their outcome [19]. A subsequent study in 1998 showed significantly lower general academic scores among 82 children with CVD as compared to 82 children with NCV, matched by age and class [20]. In contrast, a 2004 cohort study on 499 CVD children found that CVD did not cause significantly lower scores in mathematics and reading at 7 years and 16 years of age respectively, even after adjusting for birth-weight, social class at birth, family size, and parental education [21].…”
Section: School Agementioning
confidence: 99%
“…This adaptation is not likely to prevent the dyschromate from feeling of lack of control on his life. In fact, we must point out that these processes start during childhood; most colour-blind children are unaware of their deficit, as already shown in former studies, with percentages ranging from 94% 23 to 96% in Italy. 24 Colour defectives could learn that events are out of their control, because they cannot actively affect the consequences-negative or positive-of their behaviour, developing a feeling of helplessness.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, Italian students with CVD and aged 10-15 years were found to present lower general school achievements, except for art, than their normal vision counterparts (Grassivaro Gallo, Oliva, Lantieri, & Viviani, 2002;Grassivaro Gallo, Panza, Viviani, & Lantieri, 1998). Similarly, colour vision deficient medical students enrolled in a histopathology course achieved a lower Learning and Individual Differences 21 (2011) …”
Section: Introductionmentioning
confidence: 88%